Pengembangan Kreativitas Pengolahan Sampah Plastik melalui Pemberdayaan Wanita di Kalisegoro Semarang - Dyah Ayu Widyastuti; Rivanna Citraning Rachmawati; Atip Nurwahyunani (Jurnal Surya Masyarakat, 2020)
Unprocessing household waste is one of environmental problem which has to be overcome by Kalisegoro society. People only depend on garbage transport service to process household waste henceforward to final disposal site. Those habit leads to unprocessing household waste in Kalisegoro and more contaminate the environment. Household waste processing training is required to enhance the ability of Kalisegoro society, especially for housewife so that the household waste can be handled well. This program intend to enhance creativity of housewife in Kalisegoro to process plastic from household waste. Plastic waste can be processed become handycrafts and reduce rubbish buildup which leads to environmental pollution. The participant of this program is household who incorporated in Dorang Dawis Anggrek 17 business unit in Kalisegoro Gunungpati Semarang.